Herd behaviour in stock markets: an international perspective - boutabba, islem ahmed (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
In this paper, we study the behavioral finance as a theory that seeks to combine cognitive and psychological components with economic and financial aspects to explain irrationality of financial decisions. It is a paradigm where financial markets are studied using models that are less tight than those based on expected utility theory of Neumann Morgenstern and on arbitrage assumptions. Behavioral finance has two main parts: cognitive psychology and the limits to arbitrage.Cognitive refers to how people think. There is a large literature in psychology that claims people make asymmetric errors in thinking. Limits to arbitration refer to prediction data where forces of arbitrage circumstances will be effective or not. Our empirical validation focused on one of the cognitive components: herding. Indeed, we examined herd behaviour in an international context (the United States (DJU), Argentina (MERV), and France (CAC20)) using the model of Chang et al (2000). Our results led us to conclude that there is no herd behaviour.